Gut-borne Saccharomyces cerevisiae, a promising candidate for the formulation of feed additives, modulates immune system and gut microbiota - Garcia, Guillermo (2016)
The aim was to evaluate the effect of Saccharomyces cerevisiae RC016 on immune parameters and gut microbiota in healthy mice. Animals received S. cerevisiae RC016 for 10 days. Microbial translocation to liver and changes in some bacterial populations in caecum were determined. Immune stimulation was assessed at gut level (measure of immunoglobulin A (IgA)+ cells and luminal cytokine profile) and by evaluating the activity of peritoneal macrophages. Oral administration of S. cerevisiae RC016 did not induce microbial translocation to liver. Mice that received yeast increased the number of IgA+ cells in their intestines, the phagocytic activity of peritoneal macrophages and decreased tumour necrosis factor alpha (TNF-α) levels in the small intestine with increases of interleukin-10/TNF-α ratio. Administration of S. cerevisiae RC016 caused the decline of a logarithmic unit for Enterobacteriaceae counts compared to the control. The immune and gut microbiota modulation observed demonstrates that S. cerevisiae RC016 is a promising candidate for the formulation of feed additives to improve animal productivity. The beneficial in vivo effects observed for the potential probiotic S. cerevisiae RC016 with previously reported mycotoxin-binding properties, demonstrated that this strain could be suitable to be included in a novel product to improve animal productivity, with both probiotic and mycotoxin-binding properties. However, studies in the specific host will be necessary to confirm this potential.